Learning from collaborative ‘conversations’ on the Students as Producer Pedagogic model: students’ views - Strudwick, Kate; Johnson, Phil (PRISM: Casting New Light on Learning, Theory and Practice, 2020)
This paper explores and reflects on the outcomes of the application of two different pedagogic models at two Higher Education institutions in the UK, University Centre at Blackburn College and the University of Lincoln. Through a set of collaborative ‘conversations’ the experiences of the pedagogic practices – from a sample of participating students – within and across the two institutions are contextualised in relation to the following projects: the Community Challenge project, developed and implemented at University Centre Blackburn College; and, the Student as Producer initiative developed and implemented at the University of Lincoln. The reflections and narratives that emerged from the collaborative conversations are grouped (and explored) via four key themes: student engagement, research skills, employability, and curriculum design; a number of similarities and differences are also highlighted in relation to the two projects. These variations support the point made by Bovill (2015: np) that ‘[i]f we constantly question ourselves and each other about partnerships, we are more likely to gain greater understanding to enhance future partnerships’. Beyond this, the paper addresses wider literature in relation to the Students as Partners (Healey, Flint and Harrington, 2014), and Students as Change agents as pedagogic approaches (Dunne & Zandstra, 2011). Finally, the paper considers whether a common pedagogic ethos can be identified.